Metabolites of Procyanidins From Litchi Chinensis Pericarp With Xanthine Oxidase Inhibitory Effect and Antioxidant Activity - Sui, Yong; Shi, Jianbin; Cai, Sha; Xiong, Tian; Xie, Bijun; Sun, Zhida; Mei, Xin (Frontiers in Nutrition, 2021)
Procyanidins from litchi pericarp (LPPC) have been evidenced to possess strong antioxidant activities in vivo, which is possibly correlated with their intestinal metabolites. However, the xanthine oxidase inhibitory effect of LPPC and its metabolites was less concerned. In the present study, 3 oligomeric procyanidins and 8 metabolic phenolic acids were identified in the urine of rats administrated with LPPC by HPLC and LC-MS analysis. Data indicated that all the metabolites excreted were significantly increased by the treatment of 300 mg/kg body weight of LPPC (P < 0.05), revealing considerable DPPH and hydroxyl radicals scavenging activities. Moreover, phenolic metabolites involving epicatechin, A-type dimer, A-type trimer, caffeic acid and shikimic acid exhibited greater xanthine oxidase inhibition effects compared with other metabolites, with inhibitory rate higher than 50% at the concentration 200 μg/mL. The IC50 value of these five phenols were 58.43 ± 1.86, 68.37 ± 3.50, 74.87 ± 1.30, 95.67 ± 3.82 and 96.17 ± 1.64 μg/mL, respectively. As a whole, this work suggests that the xanthine oxidase inhibition and antioxidant activity of LPPC-derived metabolites as one of the mechanisms involved in the beneficial effects of LPPC against hyperuricemia or gout.